Preventive and therapeutic role of functional foods: a review (International Journal of Food and Nutritional Sciences, 2022)
Functional foods are those that are whole, enhanced, fortified, or improved and are consumed at beneficial levels as part of a nutrient-dense diet on a regular basis to provide therapeutic advantages beyond the provision of basic nutrients (e.g., minerals and vitamins). However, not all foods marketed as "functional foods" today are supported by enough data to back up such claims. Functional foods include things like fruits and vegetables, as well as foods that have been augmented or fortified. Functional foods have biologically active ingredients that provide positive physiological effects or health benefits. Functional foods should be a part of a balanced diet to meet nutritional needs and safeguard the body from many illnesses and disorders as diabetes, cancer, obesity, cardio vascular disease, etc. It is utilized in food supplements and generally in nutraceuticals (including probiotics, prebiotics, synbiotics etc). Probiotics, prebiotics, and functional foods rich in a variety of nutrients also play an important part in daily living in addition to these nutraceuticals. The functional qualities of many traditional meals are being investigated, and new food products containing healthy ingredients are being created. One of the areas of the food and nutrition sciences that is currently receiving the greatest research and promotion is functional foods. The goal of the current review study is to incorporate the therapeutic and preventative functions of functional food.